Shielding of electromagnetic radiation by multilayer textile sets. Issue 6 (March 2019) - Marciniak, Katarzyna; Grabowska, Katarzyna Ewa; Stempień, Zbigniew; Ciesielska-Wróbel, Izabela Luiza
This paper presents the continuation of research on shielding efficiency (SE) of electromagnetic radiation (EMR) by woven fabric made of cotton (warps and wefts) and a hybrid yarn (wefts). This hybrid yarn was made of stainless steel yarn by Bekinox wrapped with an enamelled copper wire from Synflex Elektro GmbH, Germany. The pitch of copper coil on a hybrid yarn equals 3 mm. The wefts were introduced into the fabric in the following order: 1 hybrid yarn, 1 cotton yarn, 1 hybrid yarn, 1 cotton yarn, etc. The construction of this specific fabric was proven to be the most efficient in terms of the hybrid weft construction and the fabric construction to shield EMR among other previously tested fabrics with different weft configuration. The current study proposes to verify the effect of the number of layers of the fabrics and their mutual configuration on the final SE of the multilayered set. Some of the most interesting findings of this study are that increasing the number of layers placed on top of one another with an offset angle of 0° to more than two does not provide a higher SE; however, using three such layers provides an SE of 56 dB, which is over two times higher than that provided by a single layer. Increasing the number of layers of fabric aligned at an angle of 45° provides a higher SE only for a frequency of 30 MHz.